A novel shark single-domain antibody targeting OGT as a tool for detection and intracellular localization - Xi, Xiaozhi; Xiao, Guokai; An, Guiqi; Liu, Lin; Liu, Xiaochun; Hao, Peiyu; Wang, Jennifer Yiyang; Song, Dandan; Yu, Wengong; Gu, Yuchao (Frontiers in Immunology, 2023)
O-GlcNAc modification is a universal protein modification that plays an important role in both cell physiology and pathology. It is now generally accepted that O-GlcNAc transferase (OGT) catalyzes the attachment of a single O-linked N-acetylglucosamine (O-GlcNAc) to the hydroxyl groups of serine and threonine residues of nuclear and cell membrane proteins. Therefore, regulation of O-GlcNAc levels by targeting OGT has been used as a therapeutic strategy. However, the study of O-GlcNAc function has been limited by the lack of tools with spatiotemporal resolution to localize and control OGT activity in cells. Antibodies have long been widely used by cell biologists to localize proteins within cells using light microscopy. The large size and flexibility of conventional antibodies places the fluorophore at randomized or unknown distance from the target proteins, limiting the accuracy and precision of super-resolution imaging techniques and making them unsuitable for monitoring dynamic processes. The small size of nanobodies derived from nurse shark or closely related species of variable immunoglobulin neoantigen receptors (VNAR) allows them to better penetrate dense intracellular cytoskeletal regions, as well as tissues, greatly expanding the possibilities of advanced cellular imaging, such as live cells or super-resolution microscopy to visualize cellular antigens and their dynamics. Therefore, we immunized the spotted bamboo shark (Chiloscyllium plagiosum) with recombinant OGT proteins and constructed a high-quality library of shark VNARs phages. Sequences of three shark VNARs (2D9,3F7 and 4G2) were obtained by solid-phase elution. Expression vector based on pET28a backbone was constructed allow for recombinant expression of indicated proteins in E. coli. The intact molecular weights of the three shark VNARS were determined using LC-MS/MS. The biotinylated VNARs can then be used for the detection and localization of OGT by ELISA and immunofluorescence. This study will provide a novel tool for the identification and high-resolution imaging of OGT.